INTERNAL AND EXTERNAL FACTORS OF ACCOUNTING STUDENTS IN THE IMPLEMENTATION OF ONLINE LEARNING DURING THE COVID-19 PANDEMIC ERA IN PEKALONGAN - Ina Mutmainah; Fachri Ali (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
The present study showcases the effect of accounting understanding level, lecturer competence, and student achievement on online learning in the Covid-19 pandemic through learning motivation. The population of this study was accounting students situated at universities in Indonesia. 153 students of a university in Pekalongan, Central Java volunteered to participate. Purposive sampling was employed, and data were garnered through questionnaires. The distributed data were processed using a Likert scale. Path analysis was carried out to analyze data. Study findings expose that the level of accounting understanding, lecturer competence, and student achievement had no effect on online learning. The level of accounting understanding and student achievement did not have a significant effect, while lecturer competence had a significant effect on online learning through learning motivation. This empirical evidence provides an overview of learning evaluation materials for higher education in Indonesia related to students’ abilities in online learning during the Covid-19 pandemic so that in the future it will be more effective and ready to compete in the digital era 4.0.